STRUKTUR PASAR PERSAINGAN PERBANKAN INDONESIA DALAM PERIODE KONSOLIDASI - Sutardjo Sutardjo; Arief Daryanto; Bustanul Arifin; D. S. Priyarsono (School of Business, Bogor Agricultural University (SB-IPB), 2011)
The objective of this study is to investigate evidence of market structure and to analyze market structure variables that influence bank revenue in the Indonesian banking market during the consolidation era. The Hirschman-Herfindahl (HHI) and Concentration Ratio Four (CR4) indices indicated decreasing trend and low level of market concentration. The test of market competition by using Panzar-Rosse approach at industry level indicating a monopolistic competition behaviors among banks. In addition,the market for interest-based income is found to be more competitive than that of for fee-based income. The study also suggest that during the consolidation period, input price of banks product seems higher. In addition, the study conclude that there is no indication of changes of the Indonesian banking market structure in the period of 1999-2009. The result of partial analysis also indicate a monopolistic competition behaviors among banks according to their ownership status. Accordingly, the market for non interest based income is found to be more competitive than that of interest based income for the Joint Venture Bank (Bank Campuran) and the Foreign Bank (Bank Asing).Keywords : Market Structure, HHI, CR4, Panzar and Rosse